A Survey of N IV and O IV Features near 3400 Å in O2-O5 Spectra - Morrell, Nidia Irene (2005)
We have conducted a survey of little-known N iv and O iv multiplets near 3400 A˚ in an extensive sample of well-classified, very early O-type spectra. The initial motivation was to search for additional useful classification criteria for these types, but an unexpected result is the high sensitivity of these features to evolutionary CNO processing. We have found a useful discriminant between O2 and later types in the relative strengths of the O iv multiplets, one of which is subject to selective emission in the hottest spectra; the overall strengths of these lines also decrease between spectral types O4 and O5. More remarkable, however, are the variations in the N/O ratios among both individual stars and clusters. For instance, several O4 If spectra have very large ratios, while main-sequence stars in the Carina Nebula generally have smaller values than others of the same spectral types in other regions. These effects correspond to different degrees of mixing of processed material as a function of evolutionary age and initial rotational velocities; the second effect provides significant further evidence that very massive stars mix while still on the main sequence. Thus, further analysis of these features will likely provide valuable diagnostics of important evolutionary parameters.